CT and MRI Findings of Autoimmune Polymorph Bifocal Pancreatitis Mimicking Pancreatic Adenocarcinoma: A Case Report and Review of the Literature. (11th March 2015) - Rotzinger, Roman; Bläker, Hendrik; Bahra, Marcus; Denecke, Timm; Grieser, Christian
Autoimmune pancreatitis is a rare type of chronic pancreatitis. It is supposed to be a pancreatic manifestation of an immune-complex modulated systemic disorder. In contrast, pancreatic adenocarcinoma is the most frequent malignant neoplasm of the pancreas. Within the rare type of focal autoimmune pancreatitis, only few presentations with multifocal pancreatic lesions have been described. Herein we report a case of a 58-year-old patient with autoimmune pancreatitis presenting with bifocal manifestations of the pancreatic head and tail, mimicking pancreatic adenocarcinoma clinically, on computed tomography and magnetic resonance imaging. Typical imaging findings of autoimmune pancreatitis are compared with typical findings in pancreatic carcinoma. The diagnostic dilemma of differentiating between both entities is discussed. A review of the present literature regarding multifocal presence of autoimmune pancreatitis is performed.